Higher education finances: How have they fared, and what options will an incoming government have? - Kate Ogden; Ben Waltmann (Institute for Fiscal Studies (IFS), 2024)
The next government faces difficult choices on higher education funding, with tuition fees frozen and international student recruitment falling.
Keywords: 330; Education and skills; Government finances and spending; Education; Government spending; Higher education